Inter-ethnic tolerance and cross-cultural communication: its relationship and importance in a multicultural society - Mei Tien, W.Y.; David, M.K. (2011)
Malaysia is a multi-cultural country, as a result of colonialism and economical geography. Such diversity makes tolerance a requirement for survival. Without tolerance, there can be a lot of tension or even conflict as a result of miscommunication in the society. Literature has demonstrated that effective inter-cultural communication is critical to the establishment of favourable inter-group relations (Gudykunst, 1986; Hall, 1976). This study aims to identify the importance and relationship of inter-ethnic tolerance and inter-cultural communication in multi-cultural Malaysia. A total of 310 undergraduates were involved in this study and the results indicated there is a positive correlation between inter-ethnic tolerance and inter-cultural communication. This study provides statistical evidence on the importance of inter-cultural communication in a multicultural society.